Machine kitsch theory: Contrasting shifts in public perceptions towards AI-generated art - Aulia Ardista Wiradarmo; Hanif Arsyad Azhar (Jurnal Desain)
The rapid integration of Generative Artificial Intelligence (GenAI) into the art world has sparked debates on its authenticity and creative value. This study investigates public perceptions of AI-generated art, focusing on changes in interest and interpretation before and after disclosure of GenAI's involvement. Grounded in theories of generative art and kitsch, it examines how GenAI evokes both admiration and criticism. Using an explanatory sequential mixed-method approach, a survey of 553 respondents evaluated interest, emotional reactions, and the ability to distinguish AI-generated from human-made artworks. Quantitative data revealed a decline in interest post-disclosure (overall mean: 5.09 to 4.75), while qualitative insights highlighted polarised views on AI’s role in art. Respondents praised GenAI’s technical sophistication and democratising potential but criticised its lack of emotional authenticity. It identifies contrasting perceptions of GenAI in art, emphasising the need for ethical considerations and a redefinition of artistic values as technology reshapes creativity and aesthetic judgement